Representasi Nasionalisme dan Patriotisme dalam Film Perburuan: Analisis Semiotika - Hanif, Randy Muhammad; Rasyid, Abdul; Azhar, Anang Anas (Medan Resource Center, 2023)
Film Perburuan is a film adapted from the novel by Pramoedya Ananta Toer titled Perburuan. The film portrays the background and conditions of Indonesia during the struggle for independence, depicting the PETA (Defenders of the Homeland) forces when they were cornered while facing the Japanese army. Richard, the screenplay writer, added a story element to the film by providing a depiction of events six months prior to the original story, focusing on the character of Hardo. Research results show that Film Perburuan, in various ways understood by researchers using the construction theory and semiotic analysis approach of Roland Barthes, has six scenes that demonstrate the function of actors, with 20 functions depicting the meaning of struggle out of 31 functions of actors. There are eight opposing characters that represent the characters of goodness and evil based on the characters in the film, and within the seven character functions, there are only six characters in Film Perburuan. In Film Perburuan, this is achieved by using the stages of denotation and connotation. The denotation stage represents the literal meaning or what happens in the scene, while the connotation stage represents the meaning used to interpret the hidden meanings present in each scene.